2014
DOI: 10.1016/j.neurobiolaging.2013.10.090
|View full text |Cite
|
Sign up to set email alerts
|

Age-related downregulation of the CaV3.1 T-type calcium channel as a mediator of amyloid beta production

Abstract: Alzheimer's is a crippling neurodegenerative disease that largely affects aged individuals. Decades of research have highlighted age-related changes in calcium homeostasis that occur before and throughout the duration of the disease, and the contributions of such dysregulation to Alzheimer's disease pathogenesis. We report an age-related decrease in expression of the CaV3.1 T-type calcium channel at the level of messenger RNA and protein in both humans and mice that is exacerbated with the presence of Alzheime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 42 publications
2
40
0
Order By: Relevance
“…An age‐related down‐regulation of Ca V 3.1 mRNA and protein expression was previously demonstrated in the brains of humans and mice (Rice et al . ). This down‐regulation of Ca V 3.1 protein might be considered to play a role in the age‐dependent effect of Ca V 3.2 channels in both MT and FMVD (e.g.…”
Section: Discussionmentioning
confidence: 97%
“…An age‐related down‐regulation of Ca V 3.1 mRNA and protein expression was previously demonstrated in the brains of humans and mice (Rice et al . ). This down‐regulation of Ca V 3.1 protein might be considered to play a role in the age‐dependent effect of Ca V 3.2 channels in both MT and FMVD (e.g.…”
Section: Discussionmentioning
confidence: 97%
“…burden, whereas overexpression of Ca v 3.1 T-type VGCC alleviates amyloidogenesis (86). Consistently, the Ca v 3.1 T-type VGCC enhancer, ST101, is reported to induce APP cleavage in vitro (87) and contribute to cognitive improvement in vivo (88).…”
Section: Vgccmentioning
confidence: 82%
“…Additionally, Ab peptides may intensify N-and P-type Ca 2+ current (83)(84)(85). As for the Ca V 3.1 T-type VGCC, its age-related down-regulation in human brain tissue was revealed by Rice et al (86), and the presence of AD exacerbates the alteration. In the subsequent experiments on 3 xTg-AD mice and cultured cells, the researchers further demonstrated that inhibition of the channel increases Ab Figure 2.…”
Section: Vgccmentioning
confidence: 99%
“…T-type channels expression is down regulated in the brain during aging and AD (Rice et al, 2014), suggesting reduced function of these channels may be key in driving calcium dysfunction in AD. Further, chronic inhibition of T-type channels increases Aβ peptide levels, suggesting T-type channel activity is linked with Aβ production.…”
Section: Discussionmentioning
confidence: 99%